Utilization of insecticide-treated nets among pregnant women in East Africa: evidence from a systematic review and meta-analysis - Lidetu Demoze; Kassaw Chekole Adane; Natnael Gizachew; Amensisa Hailu Tesfaye; Gelila Yitageasu (BMC Public Health)
Abstract Background The World Health Organization (WHO) advocates the use of insecticide-treated nets (ITNs) as a primary strategy for malaria control during pregnancy. Despite these recommendations, ITN utilization among pregnant women in endemic regions, particularly East Africa, remains lower and inconsistent. This systematic review and meta-analysis comprehensively examined individual studies to provide a more robust and reliable estimate of ITN utilization among pregnant women in the region. Therefore, this systematic review and meta-analysis aimed to determine the pooled prevalence of ITN utilization among pregnant women in East Africa. Methods We conducted a comprehensive literature search to identify studies on insecticide-treated bed net utilization among pregnant women in East Africa. We searched the Medline/PubMed, Embase, Scopus, Science Direct, Epistemonikos, Google Scholar, and Google manual databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. We used predefined inclusion criteria to screen identified studies. Heterogeneity across the studies was evaluated via Cochrane Q test statistics and the I2 test. A random effects model was computed to estimate the pooled prevalence of ITN utilization among pregnant women in East Africa. Results After a systematic review of 11,509 studies, 35 studies met the inclusion criteria and were included in the meta-analysis. The findings from the 35 studies revealed that the pooled prevalence of ITN utilization among pregnant women in East Africa was 51.6% (95% CI: 42, 61). Subgroup analysis revealed that the highest prevalence of ITN utilization was observed in South Sudan (89%), and the lowest was in Sudan (12%). Conclusions This review revealed that a significant proportion of pregnant women in East Africa did not use ITNs. In addition, there was significant variation in ITN utilization among pregnant women across East African countries. These findings indicate a need for tailored interventions to address these disparities.